Cutaneous and ocular signs in a calf infected with Theileria annulata -case report - Tumer, Kenan Çagrı; Karabulut, Burak; Ulucesme, Mehmet Can (Kastamonu Üniversitesi, 2022)
Tropical theileriosis is an important tick-borne disease in cattle that is caused by an obligate intracellular protozoan, Theileria annulata (T. annulata). In addition to the common clinical signs of tropical theileriosis such as pyrexia, lymph node enlargement, conjunctival petechiae, and anemia, veterinary practitioners may encounter unexpected clinical signs such as skin nodules and bilateral exophthalmos due to conjunctival edema. The main purpose of this report is to present clinical manifestations and histopathological findings of extensive cutaneous nodules and conjunctival edema in a calf infected with T. annulata.
Keywords: Veterinary Surgery; Veteriner Cerrahi